Cabozantinib Reverses Topotecan Resistance in Human Non-Small Cell Lung Cancer NCI-H460/TPT10 Cell Line and Tumor Xenograft Model - Lei, Zi-Ning; Teng, Qiu-Xu; Gupta, Pranav; Zhang, Wei; Narayanan, Silpa; Yang, Dong-Hua; Wurpel, John N. D.; Fan, Ying-Fang; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2021)
Cabozantinib (CBZ) is a small molecule tyrosine kinase receptor inhibitor, which could also inhibit the ABCG2 transporter function. Therefore, CBZ could re-sensitize cancer cells that are resistant to ABCG2 substrate drugs including topotecan (TPT). However, its reversal effect against TPT resistance has not been tested in a TPT-induced resistant cancer model. In this study, a new TPT selected human non-small cell lung cancer (NSCLC)-resistant cell model NCI-H460/TPT10 with ABCG2 overexpression and its parental NCI-H460 cells were utilized to investigate the role of CBZ in drug resistance. The in vitro study showed that CBZ, at a non-toxic concentration, could re-sensitize NCI-H460/TPT10 cells to TPT by restoring intracellular TPT accumulation via inhibiting ABCG2 function. In addition, the increased cytotoxicity by co-administration of CBZ and TPT may be contributed by the synergistic effect on downregulating ABCG2 expression in NCI-H460/TPT10 cells. To further verify the applicability of the NCI-H460/TPT10 cell line to test multidrug resistance (MDR) reversal agents in vivo and to evaluate the in vivo efficacy of CBZ on reversing TPT resistance, a tumor xenograft mouse model was established by implanting NCI-H460 and NCI-H460/TPT10 into nude mice. The NCI-H460/TPT10 xenograft tumors treated with the combination of TPT and CBZ dramatically reduced in size compared to tumors treated with TPT or CBZ alone. The TPT-resistant phenotype of NCI-H460/TPT10 cell line and the reversal capability of CBZ in NCI-H460/TPT10 cells could be extended from in vitro cell model to in vivo xenograft model. Collectively, CBZ is considered to be a potential approach in overcoming ABCG2-mediated MDR in NSCLC. The established NCI-H460/TPT10 xenograft model could be a sound clinically relevant resource for future drug screening to eradicate ABCG2-mediated MDR in NSCLC.